Synthesis and Development of One-part Rock-based Geopolymers for Well Cementing Applications - Omran, Mohamed (Stavanger : University of Stavanger, 2023)
A one-part or Just Add Water (JAW) geopolymer system is an environmental- and user-friendly alternative to Ordinary Portland Cement (OPC) and conventional geopolymers. It helps with producing lower CO2 emissions avoiding OPC processing and eliminating the need for unnecessary liquid transportation for conventional geopolymers. A one-part geopolymer is ideal for large-scale deployment of geopolymers in well-cementing applications. It can help with quality control processes and reduce the need for extensive end-user knowledge of the chemistry involved. Accordingly, this study is to design a successful one-part naturally occurring (i.e., unprocessed nor pre-processed) granite-based geopolymer formulation. It aims to understand all possible impacts on the performance of these geopolymers of the utilized components including precursors, activators, water content and chemical admixtures. It is also to take into account petroleum engineering standards. This research is part of the SafeRock Project which is in collaboration between the University of Stavanger and operator and service companies. Additionally, it is done with a tight collaboration with academic institutes including Delft University of Technology (TU Delft, Netherlands), Universidade Federal do Rio de Janeiro (UFRJ, Brazil) and University of Oklahoma (OU, United States). The outcomes of this thesis have been published in seven scientific articles: four journal papers, two peer-reviewed conferences, one SPE conference, and a filed patent application in Norway and PCT application in Europe. This section is composed of a brief description of the published articles and their scientific findings. The outcomes of this research can be summarized as the following: Paper I shows the normalization of a Norwegian grounded granite in the solid phase by slag, microsilica, potassium silicates and alkali-metal hydroxides. It illustrates the synthesis of a one-part granite-based geopolymer for well-cementing applications (JAW). It reveals the chemical composition of ...